Skin closure after laparotomy with staples or sutures: a study of the mature scar. Issue 9 (1st July 2013) - Simcock, Jeremy W.; Armitage, Jon; Dixon, Liane; MacFarlane, Kim; Robertson, Greg M.; Frizelle, Frank A.
Abstract Background Surgeons are divided in their method of choice for skin closure following laparotomy. We suggest that the most important determinant should be the resulting scar. This study aims to compare both patients' and independent observers' assessment of mature laparotomy scars that had been closed with either subcuticular sutures or external staples. Methods Consecutive patients were enrolled at least 1 year following colorectal surgery. Scars were assessed with the validated Patient and Observer Scar Assessment Scoring (POSAS) tool. Photographs were assessed by a blinded independent panel. Results Overall, 232 patients were enrolled (90 suture, 143 staples). The two groups were well matched by factors affecting wound healing. Patients' overall opinion of their scar was significantly better for the Suture group than the Staples group (P = 0.028) despite there being no difference in their self‐assessment of the components of their scar score (pain, itch, colour, stiffness, thickness, irregularity). The panel recorded similar overall scores for the Suture and Staples groups (P = 0.059). There was a significant lower (better) score recorded for the scar area component for the Suture group than the Staples group (P = 0.008) but no differences for the other components (vascularity, pigmentation or thickness). Discussion This study has shown that independent of skin closure method, patients who have undergone major abdominal surgery have a positive opinion of their mature scars. The patients' overall impression of the wound favours a sutured closure due to a smaller scar area (no staple marks). In all other respects, skin closure with staples would appear acceptable.